2018
DOI: 10.1007/s00216-018-1105-8
|View full text |Cite
|
Sign up to set email alerts
|

Tracking emerging mycotoxins in food: development of an LC-MS/MS method for free and modified Alternaria toxins

Abstract: Mycotoxins produced by Alternaria fungi are ubiquitous food contaminants, but analytical methods for generating comprehensive exposure data are rare. We describe the development of an LC-MS/MS method covering 17 toxins for investigating the natural occurrence of free and modified Alternaria toxins in tomato sauce, sunflower seed oil, and wheat flour. Target analytes included alternariol (AOH), AOH-3-glucoside, AOH-9-glucoside, AOH-3-sulfate, alternariol monomethyl ether (AME), AME-3-glucoside, AME-3-sulfate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 51 publications
3
83
1
1
Order By: Relevance
“…The used standard of alternariol from Alternaria species (AOH) had a purity of ≈96 % and was purchased from Sigma-Aldrich (St. Louis, MO). To check for impurities with structural analogy LC-MS measurements according to Puntscher et al [19] were conducted and revealed the presence of 2.1-3.4% of alternariol monomethyl ether (AME). Stock solutions of AOH and dexamethasone (Dex, HPLC ≥ 98%; Sigma-Aldrich) were prepared in DMSO (Carl Roth GmbH&Co., Karlsruhe, Germany).…”
Section: Chemicalsmentioning
confidence: 99%
“…The used standard of alternariol from Alternaria species (AOH) had a purity of ≈96 % and was purchased from Sigma-Aldrich (St. Louis, MO). To check for impurities with structural analogy LC-MS measurements according to Puntscher et al [19] were conducted and revealed the presence of 2.1-3.4% of alternariol monomethyl ether (AME). Stock solutions of AOH and dexamethasone (Dex, HPLC ≥ 98%; Sigma-Aldrich) were prepared in DMSO (Carl Roth GmbH&Co., Karlsruhe, Germany).…”
Section: Chemicalsmentioning
confidence: 99%
“…ATXII is well known to be formed by Alternaria alternata strains in vitro, i.e., in rice-based culture (Schwarz et al 2012; Zwickel et al 2016a). However, data concerning its occurrence in food and feed are limited and great effort is continuously devoted to the development/optimization of analytical methods for its detection (Puntscher et al 2018; Zwickel et al 2016b). To add complexity to this scenario, actual data indicate that ATXII may promptly react with food constituents (Aichinger et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of DAC-EuChemS objectives is to support its delegates on the organization of local events open to the international community through dissemination of the event within the Professional Network. In 2019 we have scheduled the 2nd Cross-Border Seminar on Electroanalytical Chemistry (CBSEC), 10…”
Section: Dac-euchems Activitiesmentioning
confidence: 99%
“…These heavy metals ions are also identified and detected using electrochemical methods in environment [7] where analytics in water plays a fundamental role regarding contaminants and upcoming antibiotics [8]. Interesting is also the measurement of mycotoxins [9] and their tracking in food using LC-MS/MS [10]. The microplastic pollution of water is an increasing issue worldwide, therefore a review on the challenges for analytical chemistry regarding the analysis of microplastics in the environment has a high citation rate [11].…”
Section: Highlights Of Research In Analytical Chemistry -2018mentioning
confidence: 99%